2020
DOI: 10.1021/acs.macromol.9b01928
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of the Spacer in Tuning the Length of Self-Assembled Nanorods

Abstract: Polymeric supramolecular nanorods were prepared in toluene by self-assembly of tris(urea) stickers connected on both sides through alkyl spacers of different lengths to short poly(styrene) (PS) arms. Several tris(urea) initiators or chain transfer agents were synthesized straightforwardly and used to grow well-defined PS arms via Atom Transfer Radical Polymerization (ATRP) or Reversible Addition Fragmentation chain Transfer (RAFT) polymerization. Self-assembly was investigated by means of FTIR and light/neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Even in this case, a q −1 dependence can be observed closer to the upper q-limit, but a plateau is formed at q values below 9 × 10 −3 nm −1 . Combining the data of both scattering techniques 52 (Figure 2A; see the Supporting Information for details), a model of a cylinder with a radius R cyl of 5.0 nm and a length L cyl of 311 nm can be fitted. A Gaussian distribution was applied to the radius to match the observed smooth oscillation at high q values, which is most likely related to the distribution and the fuzzy nature of the PEO shell with solvated chains reaching into the solvent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Even in this case, a q −1 dependence can be observed closer to the upper q-limit, but a plateau is formed at q values below 9 × 10 −3 nm −1 . Combining the data of both scattering techniques 52 (Figure 2A; see the Supporting Information for details), a model of a cylinder with a radius R cyl of 5.0 nm and a length L cyl of 311 nm can be fitted. A Gaussian distribution was applied to the radius to match the observed smooth oscillation at high q values, which is most likely related to the distribution and the fuzzy nature of the PEO shell with solvated chains reaching into the solvent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The design of many supramolecular core units within such nanostructures relies on a combination of hydrophobic elements repelling the aqueous environment with multiple strong H‐bonding units, as demonstrated, for example, for urea based sticker motifs, the benzene/toluene bisureas, squaramides or 1,3,5‐substituted benzene units featuring either amide, urea, or peptide units. [ 12–27 ] Considering the latter, we have previously shown that the number of H‐bonds per central motif, and thus the interaction strength, is decisive to obtain SPBs. [ 28–30 ] However, next to the strength of the supramolecular interaction and the main axial assembly, a lateral assembly appears to be crucial for the formation of cylindrical structures, which is similarly observed for other of the above‐mentioned motifs.…”
Section: Methodsmentioning
confidence: 99%
“…83 In the same way, Bouteiller and coworkers have recently prepared supramolecular nanorods by the selfassembly of tris(urea) stickers connected on both sides through alkyl spacers of different lengths to short PS arms. 84 They have shown that long supramolecular nanorods can be obtained when a nine carbons spacer is used, whereas five times shorter nanorods are achieved with a spacer of only five carbons, and even only spherical nanoparticles are formed in the absence of the spacer. This is attributed to the spacer's hydrophobic shielding of the hydrogen bonding associations.…”
Section: Hierarchical Assembly Into Ordered Structuresmentioning
confidence: 99%